PRB Stick to facilitate stabilization of ultrasound probe and prevent work-related musculoskeletal disorder - Bhattarai, Prajjwal Raj; Regmi, Ashim (Journal of Society of Anesthesiologists of Nepal, 2019)
The authors propose a stabilizing aid to support arm of anesthesiologist during ultrasound guided procedures in the operating room.